(untitled) (Journal of Economic Research & Business Administration, 2016)
The problem of competitiveness requires a specific methodological and theoretical approaches. At the present time predominate things to achieve the competitiveness of products are replacement of obsolete equipment, modernization and technical re-equipment; reduction of production costs; investment attractiveness; the production of goods to the general public. This article analyze the current state of production from cotton raw, the state support to production of cotton is analyzed. The work is considered from the problem of competitiveness of production of cotton branch of the Republic of Kazakhstan. The main ways of permission of this problem offer modern-ization and also measures for decrease in costs of production and measures for increase of investment appeal of branch. It is emphasized that the cotton cluster of the Southern Kazakhstan region (SKR) has obvious potential for the successful competition as in the regional, and international markets.